Análise de assunto no processo de indexação: um percurso entre teoria e norma - De Sousa, Brisa Pozzi [UNESP]; Lopes Fujita, Mariangela Spotti [UNESP] (My University, 2014)
Considered the step that constitutes the intellectual work of the indexer, the approach runs the focus of the initial phase of the indexing process - the subject analysis. Among the various denominations that can be achieved, the subject analysis reaches its dimension applied when observed the rules that underlie the indexing process. The release of the documentary information requires the development of contributions to aid in the procedures of analysis, synthesis and representation of the contents documentary, seeking contributions to both the theoretical sedimentation, and for fostering the professional practice of the librarian. Through bibliographic exploratory research, this article aims to contribute to the relevance of subject analysis, concluding that there is a gap in the use of NBR 12676/1992, as well as the need for its updating.
Analysis of topic in case of index: A journey between theory and standard
Keywords: Documentary reading; Indexing - NBR 12676/1992; Indexing - Theory; Subject analysis